The mediation role of physical fitness in association between muscle-strengthening physical activities and its component with blood pressure among young adults: considering gender and abnormal blood pressure as moderators, moderate-vigorous physical activity, sleep behavior, sedentary behavior, mental wellbeing and BMI as covariates - Hidayat, Mumtaz Maulana; Agustiningsih, Denny; Sabirin, Rahmaningsih Mara; Wibowo, Rakhmat Ari (Frontiers in Cardiovascular Medicine, 2023)
Background Global burden of hypertension among young people continues to increase. There have been many studies examining the effect of aerobic and muscle-strengthening physical activity on blood pressure, many of them didn't consider interdependence between them. Conflicting results of health-related fitness, particularly handgrip strength, as intermediate outcomes of muscle-strengthening physical activity on blood pressure also emerged. This research will carry out a mediation-moderation analysis to find out the relationship between muscle strengthening physical activity and blood pressure among young adults by considering health-related fitness and 24-hour movement behavior. Methods A cross-sectional study among 221 Indonesian young adults attending a physical activity intervention collected participant's muscle-strengthening physical activity, and 24 h movement behavior, including aerobic physical activity, sedentary and sleep behavior, and mental well-being using validated questionnaires. Mediation and moderation analyses were conducted using Process Macro model 10 on SPSS 25 to investigate the association of muscle-strengthening physical activity on blood pressure, with gender and blood pressure as moderator, mediators consist of handgrip strength, muscle mass percentage and cardiorespiratory fitness. A subgroup analysis was conducted based on participant's cardiorespiratory fitness level. Results Volume of muscle-strengthening physical activities in a week have a direct association with systolic blood pressure among prehypertensive male with an effect of 0,00989359 (95% CI 0,0046488 to 0,00336478). Considering its volume as mediator, the frequency of muscle-strengthening physical activity contributed to a significant direct effect on diastolic blood pressure in both genders, but the duration of MSPA has a significant direct effect on systolic blood pressure in male subjects. There is no component of physical fitness that provides a significant mediating effect. After a subgroup analysis, the relationship between MSPA Volume and blood pressure is not significant for individuals with a high level of cardiorespiratory fitness. Conclusions This study shows that increased participation in muscle strengthening physical activity, especially in subject with low cardiorespiratory fitness, could increase blood pressure in prehypertensive young adult male population without mediation by physical fitness. Further research is needed to investigate other mechanisms that influence this relationship.